Trauma Exposure and Mental Health Problems Among Adults in Central Vietnam: A Randomized Cross-Sectional Survey - Do, Trang Thi Hanh; Correa-Velez, Ignacio; Dunne, Michael P. (Frontiers in Psychiatry, 2019)
Background: There is relatively little evidence about the psychological and social impacts of trauma exposure in the general population in East Asian countries. Vietnam has a long history of war and poverty, is prone to natural disasters and has high mortality related to traffic accidents. The mental health systems may be inadequate to cope with the resultant trauma. Objectives: This research examines the lifetime prevalence of single and multiple traumas, and the association between trauma exposure and depression, anxiety and post-traumatic stress disorder (PTSD) among a randomly selected sample of the adult population in Thua Thien-Hue province in central Vietnam. Methods: Six hundred and eight Vietnamese adults aged 18 years or older participated in the survey. The main tools in the face interview included the Life Event Checklist (LEC) to measure trauma exposure, the Hospital Anxiety and Depression Scale (HADS) and the Post-Traumatic Stress Disorder Checklist for DSM-IV– specific version (PCL-S). Hierarchical multiple logistic regression was used to examine associations between trauma exposure and mental health. Results: Forty seven percent of the participants experienced at least one traumatic event in their lifetime and about half of these people were exposed to multiple traumas. The prevalence of depression, anxiety and PTSD symptoms among the total sample was 12.7%, 15.5% and 6.9%, respectively. Prevalence of PTSD among those reporting trauma exposure was 14.8%. Exposure to a higher number of trauma types was associated with increased risk of having depression, anxiety and PTSD symptoms; those with 5+ trauma types were five to seven times more likely to report such symptoms than people with no or lesser trauma exposure. Conclusion: Our findings indicate high burden of lifetime trauma and mental ill health in the adult population of central Vietnam and a cumulative effect of multiple traumas on symptoms of the three mental disorders. Efforts to improve mental health in Vietnam should include prevention of traumatic events in every stage of life and ensure greater availability of trauma-sensitive mental health programs and services.